TACTICAL DECISION MAKING TERKAIT DENGAN KEPUTUSAN SELL OR PROCESS FURTHER PRODUK GYPSUM MENGGUNAKAN PENDEKATAN DIFFERENTIAL ANALYSIS - Sigit Pribadi; Sri Gunawan (JURNAL STIE SEMARANG, 2019)
Gypsum is a by-product of phosphoric acid production, which is a solid waste from the extraction of P2O5 content in phosphate rock. Gypsum can be directly sold as bulk gypsum (split off point) or furtherly processed into purified gypsum. Similarly, purified gypsum can also be furtherly processed into granulated gypsum which has the lowest water and P2O5 content. A differential analysis based on the use of relevant cost data is needed to identify alternatives that provide the greatest benefits to the company, related to alternative decisions to sell gypsum at the split-off point or to process it further. his study aims to develop a differential analysis that is used as a basis for tactical decision making related to the decision to sell gypsum products at the split-off point or to be furtherly processed into purified gypsum and/or granulated gypsum. This study uses a qualitative research approach while the research method used is a case study research method. The result shows that the decision to furtherly process gypsum into purified gypsum and granulated gypsum generates additional profit compared to selling gypsum at the split-off point. The production and sales of granulated gypsum generate the highest profit compared to purified gypsum and bulk gypsum at the split-off point